Sensitivity and specificity of a lateral flow immunoassay (LFI) in serum samples for diagnosis of melioidosis. (14th September 2018) - Wongsuvan, Gumphol; Hantrakun, Viriya; Teparrukkul, Prapit; Imwong, Mallika; West, T Eoin; Wuthiekanun, Vanaporn; Day, Nicholas P J; AuCoin, David; Limmathurotsakul, Direk
Abstract: Background: Culture is the gold standard for the diagnosis of melioidosis, an infection caused by Burkholderia pseudomallei. Here we evaluate a lateral flow immunoassay (LFI) to detect B. pseudomallei capsular polysaccharide (CPS) in serum samples. Methods: Patients with culture from any clinical specimen positive for B. pseudomallei were selected as cases. Patients who were blood culture positive for Staphylococcus aureus, Escherichia coli or Klebsiella pneumoniae as well as those who were malaria or dengue polymerase chain reaction assay positive were selected as controls. Results: The sensitivity of the LFI was 31.3% (60/192 case patients [95% confidence interval CI 24.8 to 38.3]) and the specificity was 98.8% (559/566 control patients [95% CI 97.4 to 99.5]) in serum samples. Conclusions: Although LFI may have limited sensitivity in serum, it can rapidly diagnose melioidosis in resource-limited settings.